Lie algebras of derivations with large abelian ideals - Klymenko, I.S.; Lysenko, S.V.; Petravchuk, A. (Algebra and Discrete Mathematics, 2019)
We study subalgebras L of rank m over R of the Lie algebra Wn(K) with an abelian ideal I ⊂ L of the same rank m over R.